Implementation of Daughters' Rights in Resolving Traditional Inheritance Disputes through Charity among The Karo Tribe (A Case Study in Nangbelawan Village, Simpang Empat District, Karo Regency) - Sebayang, Kristina; Lubis, Anggreni Atmei; Kartika, Arie (Universitas Medan Area, 2023)
The position of daughters in the inheritance distribution system based on Karo customary law in Nangbelawan Village stipulates that daughters do not inherit. When they receive an inheritance in the form of Pemere (gift) from male relatives, this provision does not ensure justice for daughters in obtaining their rightful inheritance. In contrast, the Civil Code and Supreme Court Jurisprudence Code No.179/K/SIP/1961 emphasize gender equality in inheritance rights, which often leads to family disputes. In cases of disputes in the village, conflict resolution is conducted through Arih-arih (consensus deliberations). This research combines normative and empirical legal studies using qualitative research methods, with secondary data sources and descriptive analysis. The findings reveal that daughters' positions in inheritance distribution differ from those of sons, with the allocation of one-third of the inheritance from brothers. The dispute resolution mechanism, Arih-arih, involves neutral mediators such as Anak Beru, Kalimbubu, and Village Heads. The customary inheritance system still prevails in the village, with limited progress in its development.